1998
DOI: 10.1017/s0143385798100329
|View full text |Cite
|
Sign up to set email alerts
|

Combining rational maps and controlling obstructions

Abstract: We apply Thurston's characterization of postcritically finite rational maps as branched coverings of the sphere to give new classes of combination theorems for postcritically finite rational maps. Our constructions increase the degree of the map but always yield branched coverings which are equivalent to rational maps, independent of the combinatorics of the original map. The main tool is a general theorem based on the intersection number of arcs and curves which controls the region in the sphere in which an o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
2

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(50 citation statements)
references
References 5 publications
0
44
0
2
Order By: Relevance
“…Pilgrim and Tan Lei showed that, if f is a rational map, these blow-ups frequently are as well [36]. We will restrict attention to cases where the initial map f is the identity, in which case the theorem becomes the following.…”
Section: Slit Mapsmentioning
confidence: 99%
“…Pilgrim and Tan Lei showed that, if f is a rational map, these blow-ups frequently are as well [36]. We will restrict attention to cases where the initial map f is the identity, in which case the theorem becomes the following.…”
Section: Slit Mapsmentioning
confidence: 99%
“…We mention in passing that we may think of f as being constructed via a two‐tile subdivision rule in the sense of Cannon–Floyd–Parry (see [, Chapter 12; ]). Alternatively, f is constructed from a Lattès map by ‘adding a flap’ or ‘blowing up an arc’ in the sense of .…”
Section: Sierpiński Carpet Rational Mapsmentioning
confidence: 99%
“…An analysis of quadratic Example #7 (see Figure 6) shows that this map has a cycle of four periodic basins meeting exactly in a common fixed point, with two of these basins meeting in an additional point which is a preimage of this fixed point. This example can be constructed by the operation of "blowing up an arc" [16]. This phenomena violates the classification of such intersections in [1], and thus leaves open the questions of just how the closures of such basins can intersect.…”
Section: Dynamicsmentioning
confidence: 99%
“…Such maps are in fact determined by their mapping scheme, and all may be constructed by the operation of blowing up an arc in a Möbius transformation. This technique of blowing up an arc given in [16] provides a way to produce new rational maps from ones of lower degree. For example, starting with z 2 − 1 one may produce six such cubic maps.…”
Section: Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation